Endoscopist-administered propofol sedation is safe - a prospective evaluation of 10,000 patients in an outpatient practice - Friedrich, Kilian; Stremmel, Wolfgang; Sieg, Andreas (Journal of gastrointestinal and liver diseases, 2012)
BACKGROUND & AIMS: Due to improved patient satisfaction and its pharmacological benefits, more endoscopic procedures are carried out with the use of propofol. However, recent rulings in the USA challenge endoscopist-administered propofol sedation. We evaluated the safety of endoscopist-administered propofol sedation in a German outpatient practice. METHODS: During a period of 65 months, we prospectively evaluated 10,000 patients who received endoscopic procedures. During 377 endoscopic procedures we performed extensive blood pressure observation. Propofol was administered via intermittent i.v. bolus titration by trained practice nurses under the supervision of the gastroenterologist. Oxygen saturation, heart rate and blood pressure were recorded constantly during the procedure and adverse cardiopulmonary events were monitored by the endoscopy team. A major respiratory event was defined as an episode of apnea or laryngospasm requiring assisted ventilation. RESULTS: 13,764 endoscopic procedures were recorded in 10,000 patients (7,349 esophago-gastro-duodenoscopies (ESD), 6,415 colonoscopies); 9,654 patients were sedated with propofol (ESD: 115 +/- 35; colonoscopy: 155 +/- 52; combined: 199 +/- 55 mg) and 346 patients had endoscopic examination without sedation. 0.03% of the patients received mask ventilation due to apnea and in 0.39% minor events of hypoxemia (oxygen saturation < 90%) were recorded. Bradycardia and arterial hypotension occurred in 0.07% and 0.24% of the patients. Patients with adverse events were significantly older than patients without (P < 0.001). CONCLUSION: The low number of adverse events recorded in this prospective study concludes that endoscopist-administered propofol sedation is a safe procedure. It does not seem likely that additional support of an anaesthetist would further improve patient's safety, and particularly cost-efficiency.